Comparative Study of Atorvastatin plus Fenofibrate versus Atorvastatin alone for its safety and efficacy in Hyperlipidemic patients - BP, Disha; Desai, Rina N; IS, Anand; CN, Patel (Indian Journal of Pharmacy Practice)
The aim of this study is to compare the efficacy and safety of combination containing Atorvastatin plus Fenofibrate (ATO+FENO) and to determine whether combination of Fenofibrate had clinically significant benefit over Atorvastatin alone (ATO) in patients with Hyperlipidemia. This is a single centric, open labelled, prospective study, involving 50 Hyperlipidemic patients of 18 years and older. Data of only Hyperlipidemic patients with Low Density Lipoprotein (LDL –C) ≥ 140 - < 250 mg/dl, High Density Lipoprotein (HDL-C) < 40 - > 60 mg/dl, Total Cholesterol (TC): 200-240 mg/dl and Triglyceride (TG): ≥ 165- < 400 mg/dl and who were prescribed either Atorvastatin 10 mg and Atorvastatin plus Fenofibrate 160 mg were included in the study. Efficacy end points included the change in LDL-C, HDL-C, TC and TG at week 12 and the safety of the treatment was also evaluated based on adverse events. Total of 50 patients were enrolled in the study but 1 patient lost follow up in ATO Group and 2 patients in ATO + FENO Group. Therefore 24 patients in ATO and 23 patients in ATO + FENO group completed study. A statistically significant reduction in LDL-C, TG and TC was seen in both the groups (Atorvastatin 10 mg and Atorvastatin plus Fenofibrate 160 mg). Similarly a statistically significant increase in HDL-C levels was observed in both the groups. ATO + FENO treatment showed a statistically significant reduction in TG at week 12 as compared to ATO alone. Decrease in LDL-C, TC, and TG were 24.86%, 24.81%, and 30.13% respectively and increasing HDL-C 42.37% in ATO + FENO group while the reduction was 21.1%, 21.31%, and 22.84% respectively and increasing HDL-C 38.2% in ATO alone group. The most common adverse events were headache, myalgia and nausea. ATO + FENO treatment showed a greater reduction in lipid parameters as compared to ATO alone (percentage change). Both treatments were well tolerated with similar incidence of adverse events. Study demonstrated that combination treatment was more effective than Atorvastatin alone in reducing LDL-C, Total Cholesterol and Triglyceride. It was also better in increasing HDL-C as compared to Atorvastatin. Statin in combination of fenofibrate may have lesser adverse effects. Thus Combination therapy seems to be a better treatment in patients having Hyperlipidemia.
Keywords: Adverse effects; Atorvastatin; Fenofibrate; Hyperlipidemia